The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.ajog.2008.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Oophorectomy as a risk factor for coronary heart disease

Abstract: Objective-To examine the relationship between bilateral oophorectomy (BSO) and risk of coronary heart disease (CHD).Study Design-We searched PubMed, EMBASE, meeting abstracts, and reference lists for studies that compared women with BSO at the time of hysterectomy to 1) women with hysterectomy and ovarian conservation, 2) naturally menopausal women, 3) premenopausal women or, 4) women with no history of hysterectomy or BSO but unreported menopausal status. The primary outcome was fatal or nonfatal CHD.Results-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
0
26
0
2
Order By: Relevance
“…A recent review in California that linked surgical menopause with cardiovascular risk failed to allow the desired meta-analysis due to the heterogeneity of the results found, also due to methodological errors of the studies 30 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review in California that linked surgical menopause with cardiovascular risk failed to allow the desired meta-analysis due to the heterogeneity of the results found, also due to methodological errors of the studies 30 .…”
Section: Discussionmentioning
confidence: 99%
“…7,18,19 A more recent 2013 study found no difference in change in cardiovascular disease (CVD) risk factors among women with or without premenopausal BSO at the time of hysterectomy, 20 and reviews have found the literature to be inconclusive. 21,22 In our model, a history of cardiovascular disease did not affect oophorectomy. This could indicate that these prior findings have not impacted clinical practice of oophorectomy, or that continued conflicting data has led clinicians to discount this information.…”
Section: Commentmentioning
confidence: 94%
“…In our view, several methodological limitations exist among studies conducted to demonstrate whether there is an association between BSO and CVD (58). Notably, women who undergo hysterectomy (regardless of ovarian status) have adverse CVD risk profile compared to those without hysterectomy (57), and a number of studies have failed to control for these factors.…”
Section: Fig 21 the Mechanism Of Menopause And Cardiovascular Diseasementioning
confidence: 99%
“…But bilateral oophorectomy eliminates ovarian hormones, and might be expected to influence CAD risk. Women who undergo hysterectomy (regardless of oophorectomy status) have an adverse CVD risk profile compared to those without hysterectomy, and BSO is linked to increasing CVD risk in some (41,(50)(51)(52)(53)(54) but not all studies (55)(56)(57)(58)(59). However, the increased CVD risk among women with BSO is limited to women who have the procedure before the average age at natural menopause (or an arbitrary age of 45 years) and those not receiving hormone therapy (51)(52)(53)(54).…”
Section: Rationale and Significance Of The Studymentioning
confidence: 99%
See 1 more Smart Citation